Foodborne Pathogens: Staphylococcus aureus and Listeria monocytogenes An Unsolved Problem of the Food Industry - Khan, Imran; Miskeen, Sumaira; Khalil, Ali Talha; Phull, Abdul-Rehman; Kim, Song Ja; Oh, Deog-Hwan (Pakistan Journal of Nutrition, 2016)
Foodborne illness is a serious threat to public health around the world. Foodborne illness is caused by the consumption of harmful bacteria in form of contaminated food. The contamination of food occurred throughout the food chain from farm to industry and from market to kitchen. During the last few decades, the number of outbreaks caused by foodborne pathogens has dramatically increased. Consumers are now demanding fresh and safe food products. Food industry has shown deep concern about the safety of foods and in response adopted a number of decontamination techniques to ensure safe food supply. Among 31 foodborne pathogens, the most common pathogens found in the foods are Staphylococcus aureus and Listeria monocytogenes. These pathogens have been contributing significantly to the foodborne outbreaks and deaths toll around the world. Control of these pathogens became a great challenge for the food industry. This review focuses on various decontamination technologies used in the food industry to ensure food safety and to prevent these pathogens in the food products.